Pemanfaatan Teknologi Odoo dalam Pemberdayaan Usaha Kuliner dan Nilai-Nilai Sosial Keagamaan di Warung Makan Banyuwangi - Meldi Manuhutu; Melda Agnes Manuhutu; Natasya Virginia Leuwol; Diki Diki; Sony Sony; Sintia Sintia; Lulu Jola Uktolseja (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This service activity aims to empower micro business actors through the use of digital technology based on the Odoo platform, as well as integrating social and religious values in daily business practices. The subject of the activity was Warung Makan Banyuwangi, a home-based culinary business that has been operating for more than a decade in Sorong City, Southwest Papua. This activity was carried out with a participatory approach that included field observations, interviews with business owners, training on the use of the Odoo application, and intensive assistance in the process of digitization and online business branding. Through training and mentoring, business owners are introduced to important features of Odoo, such as product management, financial transaction recording, inventory management, and promotions through online stores. The results show that the use of Odoo is able to significantly improve operational efficiency, regularity in business information management, and expand market reach through digital media. This transformation opens up new opportunities for the development of micro businesses in a more professional and modern manner. However, the success of this digital transformation does not only depend on the technical aspect, but also on the strength of the values embedded in business actors. Religious values such as honesty in transactions, sincere service, social responsibility to customers, and gratitude for business results are the main foundations in business practices. These values are not only maintained, but also integrated into the narrative displayed on the business's digital pages as an identity and differentiator. This activity proves that the digital transformation of MSMEs can go hand in hand with the preservation of local spiritual and cultural values. Technology is not only a tool for modernization, but also a medium to strengthen the identity, character, and sustainability of micro businesses in the midst of the challenges of the digital era. Therefore, collaboration between technological innovation and social values is the key to empowering community-based MSMEs.